2018
DOI: 10.23965/ajec.43.1.04
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Dream? Natural Elements, Risk and Loose Parts in Children's Dream Playspace Drawings

Abstract: IN THIS PAPER, CHILDREN'S idealised playspace drawings, arising from their participation in planning a children's playground in a local shopping centre, are examined. This examination is conducted by engaging with theories of human/nature connection, significance of place, and children as agents in co-construction of playspaces. Analysis of the drawings—through a combination of iterative visual methods and children's narratives—highlights the value children place on being outdoors and on natural elements, loos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 34 publications
2
28
0
2
Order By: Relevance
“…The theory of affordance has also been applied to young children’s motor learning contexts [10] as well as explaining PA in children, in terms of outdoor play [11], independent mobility [11,12] and the amount of affordances in the environment [13]. Previous research has shown that children find outdoor environments stimulating and motivating [12,14,15], for example, large yards that provide affordances to play and run [16]. Indeed, free running and playing are important for the development of locomotor (LM) skills, such as walking, running, climbing, galloping and jumping [17].…”
Section: Introductionmentioning
confidence: 99%
“…The theory of affordance has also been applied to young children’s motor learning contexts [10] as well as explaining PA in children, in terms of outdoor play [11], independent mobility [11,12] and the amount of affordances in the environment [13]. Previous research has shown that children find outdoor environments stimulating and motivating [12,14,15], for example, large yards that provide affordances to play and run [16]. Indeed, free running and playing are important for the development of locomotor (LM) skills, such as walking, running, climbing, galloping and jumping [17].…”
Section: Introductionmentioning
confidence: 99%
“…on logs), rolling (e.g. down a grassy hill), and children have expressed a wish for nature spaces and nature features in order to engage in active and challenging play (Brussoni et al 2020;Jansson 2015;Ward 2018). In the present study, some of the participating ECEC institutions had limited or no access to natural spaces within their playground.…”
Section: Discussionmentioning
confidence: 88%
“…Children have a preference for play where they can manipulate, explore and construct with materials such as water, stones, sand, tools, leaves, twigs, dirt, flowers, tires, ropes, toys, etc. (Brussoni et al 2020;Jansson 2015;Ward 2018;Zamani 2016). Looking at spaces that promote constructive play, the results show that nature spaces and sandboxes afford opportunities for constructive play.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations